Evolution of aesthetic rhinoplasty: an analysis of surgical techniques and outcomes at the Dr. Eduardo Liceaga General Hospital of Mexico (2019-2025) - Chamin, Correa Dip Elliott; Vianney, Díaz Avila Diana; Diego, López Gutiérrez; Raymundo, Torres Piña; Antonio, Ugalde Vitelly Juan (International Journal of Research in Medical Sciences, 2025)
Background: Rhinoplasty is a highly sought-after surgical procedure that has evolved with the concepts of function and aesthetics, achieved through precise modification of bony and cartilaginous structures using both open and closed approaches. To analyze the surgical techniques employed in aesthetic rhinoplasty between 2019 and 2025 at the Hospital General de México Dr. Eduardo Liceaga (HGM). Methods: A retrospective, descriptive, observational study was conducted on 300 patients who underwent rhinoplasty. Demographic data, type of rhinoplasty (primary/secondary), surgical approach (open/closed), incisions, osteotomies, grafts and complications were organized and analyzed within an excel table. Patient satisfaction was assessed via telephone surveys. Results: The sample was predominantly female (65%) with a mean age of 34.5 years. The majority underwent primary rhinoplasty (82%). Open and closed approaches were distributed almost equally (52% vs. 48%). The complication rate was 12%, with no significant differences between the two approaches. Overall satisfaction was high (8.5/10 for function and 8.0/10 for aesthetics), with a slight trend toward greater aesthetic satisfaction with the open approach. Conclusions: The choice between open and closed approaches should be based on nasal anatomy, patient goals and the surgeon’s experience. Both techniques produce satisfactory results, underscoring the importance of minimizing complications to improve patient perception.